Analysis of individual mistakes in the tactical performance of the defense and the relationship of goals recorded futsal football - MOHAMMED, ABDALIJAAFAR; ANALWAN, HASSAN FARH; ANALWAN, HASSAN FARH; IRHAYYIM, THAMER KADHIM (International Journal of Psychosocial Rehabilitation, 2020)
It demonstrated the importance of research by the repeated mistakes in the tactical performance of individual defense committed during the games as well as knowledge related to those mistakes recorded the goals of her puppies.The research problem came in the diagnosis of the mistakes of individual tactical performance in the defense of the iraq clubs and players know how these mistakes goals recorded from her puppies past the defender. The aims of the research is to identify the mistakes in the tactical performance of the individual in the defense of the players sample teams, either research sample included players participating clubs in the premier league football teams halls were processing the search results statistically, in the fourth quarter was the presentation and discussion of results, in chapter v it was the most important conclusions, the mistakes of the appearance of the tactical performance in the defense of individual players sample search teams. The most important recommendations was to increase the share of individual training in the defense under conditions similar to the conditions of competition.